Role of homeopathy in the Treatment of Renal Conditions: A Retrospective Study - Varghese, George Joshy (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2019)
The paper discusses the role of homeopathic medicines cates in the acute renal conditions.